Knowledge, attitude, and practice regarding cholera among non-academic staff of International Islamic University Malaysia Kuantan Medical Campus - Mohd Rosdi, Mohd Amir Fitrie; A Rahman, Nor Azlina; Haque, Mainul (Ibn Sina Trust, 2019)
Background: Cholera is a water and food-borne infectious disease caused by Vibrio cholerae. Cholera usually causes fatality in the case of severe infections. Furthermore, cholera outbreaks are still recurring over time, especially in many developing countries. Cholera outbreak may be due to lack of basic knowledge, awareness and preventive attitude among public. The objectives of this study are to evaluate the knowledge, attitude and practice (KAP) regarding cholera among non-academic staff of IIUM Kuantan community, to find the related factors of KAP regarding cholera and to find the association between KAP regarding cholera. Methods: This was a questionnaire-based cross-sectional study. This study used convenience sampling. The sample size for this study is 100 and was analyzed by using SPSS software using various tests. Those tests were independent t-test, Mann-Whitney test, Kruskal Wallis test and correlation test. There are six independent variables affecting knowledge, attitude and practice regarding cholera which are genders, marital statuses, and categories of occupation, different faculties, age-groups and level of education. Results: Categories of occupations showed no significant difference between administrative and clinical staff knowledge (p=0.360) and practice (p=0.437) level. Respondent’s attitude however showed significant difference (p=0.034) between clerk and clinical staff. As for other sociodemographic variables, the results showed no significant difference for knowledge, attitude and practice level. The results showed low positive correlation between knowledge and practice regarding cholera (r=0.338), between attitude and practice regarding cholera (r=0.331) and between knowledge and attitude (r=0.233). Conclusions: KAP practice scores were at an acceptable level.